2020
DOI: 10.3390/ijerph17165702
|View full text |Cite
|
Sign up to set email alerts
|

Health Literacy Varies According to Different Background Disease Natures and Characteristics of Participants for Patient Support Groups

Abstract: Introduction: Patient support groups (PSGs) should be designed according to the backgrounds of participants and the nature of their diseases. Using health literacy as an outcome indicator for PSGs is rare. Methods: All questionnaires (Mandarin Multidimensional Health Literacy Questionnaire, MMHLQ) were collected from eight PSGs to evaluate the health literacy of participants. Background data of participants were also collected, including patient or family, age, and first-time participation or not. Results: A t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 31 publications
(35 reference statements)
0
9
0
Order By: Relevance
“…Also, this is the first study which used the HLVa questionnaire to assess vaccine literacy functional and interactive-critical skills and its associated demographic factors in these patients. It is important to underline that previous studies conducted in patients with autoimmune diseases have used tools to assess general health literacy but not exactly to evaluate vaccine literacy (Katz et al, 2021;Maheswaranathan et al, 2020;Wu et al, 2020). Future researchers should consider using Online Photovoice (OPV) to further research this topic.…”
Section: Discussionmentioning
confidence: 99%
“…Also, this is the first study which used the HLVa questionnaire to assess vaccine literacy functional and interactive-critical skills and its associated demographic factors in these patients. It is important to underline that previous studies conducted in patients with autoimmune diseases have used tools to assess general health literacy but not exactly to evaluate vaccine literacy (Katz et al, 2021;Maheswaranathan et al, 2020;Wu et al, 2020). Future researchers should consider using Online Photovoice (OPV) to further research this topic.…”
Section: Discussionmentioning
confidence: 99%
“…Later, we cataloged these scores into four levels: inadequate (≤25), limited/problematic (25 ≤ 33), sufficient (33 ≤ 42), and excellent (42 ≤ 50). Several studies have demonstrated that the MMHLQ is an adequate tool for health literacy (16)(17)(18). In addition, the Cronbach's alpha reliability of MMHLQ was 0.79 (alpha if item deleted was 0.77-0.94) which represented an acceptable range.…”
Section: Independent Variablementioning
confidence: 99%
“…At the end of the third year, we again gave a poster presentation at the International Forum on Quality and Safety in Healthcare 24 th conference ((jointly organised by the Institute for Healthcare Improvement (IHI) & BMJ)), entitled "The evaluation of health literacy among patient support groups in a medical center". We then published a study, entitled "Health Literacy Varies According to Different Background Disease Natures and Characteristics of Participants for Patient Support Groups" [21]. We found out that the background status of participants varied according to different diseases.…”
Section: Domentioning
confidence: 99%